Therapeutic Practices of Sound Healing to Enhance Spiritual Well-being - Sharma, Soni (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2024)
The purpose of this conceptual paper is to discuss therapeutic practices of sound healing and current study related to wellness tourism development. Wellness comprises sense of well-being and sees a person as consisting body, mind and spirit (Konu, 2010). It is believed that the term wellness has emerged from the WHO notion of well-being and the concept of fitness (Koncul, 2012; Price & McCallum, 2015). In term of well-being usually lacking in clarity with the same meaning; one example; it define as an individual’s physical, mental, social, and environment status with each aspect interacting (Kiefer, 2008, p. 244). Wellness in some countries like Germany, Austria and Switzerland considerable emphasis on medical wellness (Voigt & Pforr, 2014). In the Central and Southeast European countries enhanced on sunshine, sea air, and thalassotherapy(M. Smith & Puczkó, 2014). Whereas, Asian countries, especially spiritual activities, including yoga, meditation, and massages are considered important daily activities (Kelly, 2012; Stausberg, 2014). The popular spiritual retreat activity are such as; meditation, yoga, and attend silence talk program at ashram or in temple (A. Ashton, 2018). Particularly, the sound healing can help spiritual and mind retreat, especially using Tibet bowl as an instrument to perform therapy for mind soul since an ancient time(Beaulieu & Perez-Martinez, 2018; Goldman, 2017; Longdon, 2020). Sound healing refers to sound bath, sound therapy, or sound meditation (Goldsby, Goldsby, McWalters, & Mills, 2022, p. 2). Sound healing or sound bath basically utilizes specific bell-like vibrational musical instrument called, singing bowls, or can use gongs and other vibrational musical instruments (Goldsby et al., 2022). Sound is fascinated therapeutic because it impacts on our nervous system and balance our health well-being (D’Angelo, 2005). Whenever possible being in a sound environment in tune with our nature in whatever form will lead toward liberation and true happiness, in turn give well-being life (D’Angelo, 2005). The paper will discuss some significant information, including; the important of sound healing and wellness tourism, then describes about Asia’s wellness market, wellness tourism and sound healing therapy, and recommendation for future research on wellness tourism destination development.